2022
DOI: 10.15376/biores.17.3.5285-5299
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of the inner part of oil palm trunk impregnated with aqueous polymer-isocyanate to subterranean termite attack

Abstract: Isocyanate impregnation was studied relative to the subterranean termite (Coptotermes curvignathus Holmgren) resistance of the inner part of oil palm (Elaeis guineensis Jacq.) trunk. Unproductive oil palm trunk was harvested and divided into top and bottom parts. Samples were isolated from the inner part of the trunk with a size of 2.5 cm x 2.5 cm x 0.5 cm. The samples were impregnated with 10% and 20% aqueous polymer-isocyanate and then heated at 60 °C for 48 h. The specimens were fed to subterranean termites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…On the other hand, MDI is an environmentally friendly and human-friendly resin commonly used in wood composite industries and has excellent physical and mechanical properties. Our previous study reported that IOPT impregnated with MDI with a concentration of 20% were proven to increase the density and its resistance to subterranean termites 18 . However, to date, there is no study on the physical and mechanical properties of impregnated and compregnated IOPT using MDI as an agent for the impregnation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, MDI is an environmentally friendly and human-friendly resin commonly used in wood composite industries and has excellent physical and mechanical properties. Our previous study reported that IOPT impregnated with MDI with a concentration of 20% were proven to increase the density and its resistance to subterranean termites 18 . However, to date, there is no study on the physical and mechanical properties of impregnated and compregnated IOPT using MDI as an agent for the impregnation.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also reported that the MDI molecule has two –N=C=O; one can expect a response with the –OH on the surface of straw particles by hot-press molding, and the other can have the same response with the adjacent straw particle surface, which can form a solid bonding in straw particles. However, MDI as an agent for impregnation of IOPT has never been reported, except for Mangurai et al 18 . As the authors reported, IOPT impregnated and compregnated with 20% MDI increased the density and its resistance to subterranean termites.…”
Section: Introductionmentioning
confidence: 99%